Total synthesis of (−)-himalensine A - Shi, H; Michaelides, I; Darses, B; Jakubec, P; Nguyen, Q; Paton, R; Dixon, D (American Chemical Society, 2017)
The first enantioselective synthesis of (-)-himalensine A has been achieved in 22 steps. The synthesis was enabled by a novel catalytic, enantioselective prototropic shift/furan Diels-Alder (IMDAF) cascade to construct the ACD tricyclic core. A reductive radical cyclization cascade was utilized to build the B ring, and end-game manipulations featuring a molecular oxygen mediated γ-CH oxidation, a Stetter cyclization to access the pendant cyclopentenone, and a highly chemoselective lactam reduction delivered the natural product target.